The effect of reflexology on the severity of pain due to breast engorgement in lactating mothers - Fatemeh Mousavi; Nahid Golmakani; Hamidreza Bahrami; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2020)
Introduction: Breast pain is one of the most common complaints of mothers in postpartum period. Breast engorgement is a major cause of breast pain in the first days after delivery. Reflexology induces deep muscle relaxation, thereby stimulating blood and lymph circulation in cells, releasing endorphins and controlling pain. This study was performed with aim to evaluate the effect of foot reflexology on the severity of breast pain due to breast engorgement in lactating mothers. Methods: This clinical trial study was performed in 2018 on 80 lactating mothers during the first to fifth days after delivery who had breast engorgement in Mashhad Health Center No. 1. Subjects were divided into two groups of foot reflexology and routine care. The severity of breast pain was determined by visual analogue scale and the subjects who scored 2 out of 10 on this scale entered to the study. The intervention group received foot reflexology once a day for 3 days and control group received routine care. Data were analyzed using SPSS software (version 24) and paired t-test, independent t-test, Mann-Whitney, Chi-square and ANOVA tests. P <0.05 was considered statistically significant. Results: Mean severity of pain after the intervention decreased in both reflexology and control groups. There was a significant difference between the two groups in mean of pain intensity. So that pain severity was significantly decreased in the reflexology group than the control group (p <0.001). Conclusion: Foot reflexology leads to more reduction in the severity of postpartum breast pain than routine care. Therefore, reflexology is recommended in the management of postpartum breast pain.